World Social and Economic Development in the Theory of Ternary Counterpoints - Mokiy Vladimir; Lukyanova Tatyana (European Scientific Journal, ESJ, 2019)
The need to adapt the process of knowledge of the world to the achievement of socially meaningful goals by society has contributed to the formation and consolidation at the genetic level of the corresponding megastructure of neuron connections in the brain. The presence of different types of knowledge indicates the presence of different subspecies of people. Subspecies of people differ in the mega-construction of neuronal connections in the brain. This particular mega-structure of neuron connections allows you to focus on the formation and perception of a strictly defined type of knowledge in the process of knowing the world. The use of methodology of the systems transdisciplinary approach makes it possible to identify the natural mechanism of interaction between various types of knowledge and various subspecies of people. This mechanism is implemented in the framework of the Ternary Counterpoint. The task of the Ternary Counterpoint is to provide “gain axioms”. Axioms of reinforcement contribute to the addition of a set of axioms that define the essence of the types of knowledge and subspecies of people. They are able to set and control, as well as maintain and develop this essence. The interaction within the framework of the Ternary Counterpoint is carried out by special people-hybrids. These people possess a hybrid megadesign of neuron connections in the brain. Such people began to be called generalists. It is possible that the emergence of departments for the training of generalists will become a distinctive feature of third-generation institutions.